Short- and Mid-Term Prognosis of Patients Undergoing Rotational Atherectomy in Aortoostial Coronary Lesions in Left Main or Right Coronary Arteries - Marine Quillot; Didier Carrié; Thibault Lhermusier; Frédéric Bouisset; Romain André; Meyer Elbaz; Jérôme Roncalli; Francisco Campelo-Parada; Nicolas Boudou (Journal of Interventional Cardiology)
Objective. To determine short-term and mid-term prognosis in patients with calcified ostial coronary lesions who underwent rotational atherectomy (RA). Background. RA was developed to facilitate stenting in complex lesions. Treatment of calcified aortoostial coronary lesions with RA appears to have poorer procedure outcomes than nonostial lesions; yet the literature on this topic is scarce. Methods. Of 498 consecutive patients who underwent RA, a total of 80 (16.1%) presented with aortoostial lesions. A comparative, monocentric study was performed between patients with aortoostial and nonaortoostial stenosis, in a retrospective registry. The primary endpoint was the procedural success rate. Secondary endpoints were the rates of major adverse cardiac and cardiovascular events (MACE) at 30 days and 24 months. Results. The procedural success rate was high and similar in patients with and without ostial lesions (96.3% vs 94.7%, p=0.78), as was the rate of angiographic complications (7.5% vs 8.4%, p=0.80). However, the 30-day mortality rate was significantly higher in the aortoostial group (11.3% vs 4.8%, p=0.04), as was the 24-month rate of MACE (43.8% vs 31.8%, p=0.04). The aortoostial location of the lesion was an independent factor associated with the occurrence of cardiovascular events at 24 months (HR = 1.52, 95% CI, 1.03-2.26, p=0.035). Conclusion. Procedural success and complication rates were similar in patients with and without aortoostial lesions. Despite a poor short- and mid-term prognosis, rotational atherectomy appears to be a feasible and safe treatment option for calcified aortoostial coronary lesions.